Citation for excellence in the director's category - Magpayo, Jose Mari (Animo Repository, 1997)
Communication Arts faculty Jose Mari Magpayo was given a Citation for Excellence in the Director's Category at the 1996 Chicago International Film Festival for his direction of The Gongs. The film was part of an episode of Hirayamanuwari, a television program for children which aims to educate and promote Filipino culture and values.